DESAIN LANSKAP JALAN PADA KAWASAN PERUMAHAN VILLA BUKIT TIDAR, MALANG-JAWA TIMUR - Lak'apu, Mieswandi Petronikus; Setyabudi, Irawan; Alfian, Rizki (Universitas Tribhuwana Tunggadewi, 2018)
Landscape is one of the most important parts in a residential area. The existence of a road landscape In a residential area is also very important for the surrounding community. In the city of Malang there are many housing, one of which is ousing Bukit Tidar-Malang. Facilities provided by the manager of housing that is educational facilities, health, mini market, environmental parks and so forth. This research was conducted in the residential area of Villa Bukit Tidar-Malang. The method used in this research is qualitative method. The concept developed in this study is the concept of space consists of the reception area (welcome area), the concept of vegetation (shade vegetation, steering, noise control), the concept of circulation (pedestrian circulation), the concept of facilities (environmental park) and the concept of activity (jogging track ). The result of this research is the image of site plan, perspective, and detail which is expected to give comfort, beauty, and aesthetics and can be enjoyed for the people who live In Bukit Tidar-Malang housing complex. Lanskap jalan merupakan satu bagian terpenting dalam suatu kawasan perumahan. Keberadaan lanskap jalan Di kawasan perumahan juga sangat penting bagi masyarakat sekitar. Di kota Malang terdapat terdapat banyak perumahan, salah satunya yaitu perumahan Villa Bukit Tidar-Malang. Fasilitas yang disediakan oleh pihak pengelola perumahan yaitu fasilitas pendidikan, kesehatan, mini market, taman lingkungan dan lain sebagainya. Penelitian ini dilaksanakan di kawasan perumahan Villa Bukit Tidar-Malang. Metode yang dipakai dalam penelitian ini yaitu metode kualitatif. Konsep yang dikembangkan dalam penelitian ini yaitu konsep ruang terdiri dari ruang penerima (welcome area), konsep vegetasi (vegetasi peneduh, pengarah, pengendali bising), konsep sirkulasi (sirkulasi pejalan kaki), konsep fasilitas (taman lingkungan) dan konsep aktivitas (jogging track). Hasil dari penelitian ini berupa gambar site plan, perspektif,dan detail yang diharapkan dapat memberi kenyamanan, keindahan, dan estetika serta dapat dinikmati bagi masyarakat yang tinggal Di perumahan Villa Bukit Tidar-Malang.